Estabilización de cuatro bebidas ancestrales envasadas fermentadas con kefír y levadura. - Pilamala Arcos, Christian Jonnathan (2020)
The present research was carried out in Latacunga canton, Eloy Alfaro parish, Salache neighborhood, at the Technical University of Cotopaxi, in Agro-industrial Engineering Major laboratories, whose main objective was to evaluate the stabilization of four ancestral beverages fermented with kefir and yeast. The methodology applied in the development of the research was to select, peel, wash, cook, ferment, rest, dilute, sift and add the stabilizers xanthan gum 0.1% and albumin 10%, pasteurize at 90°C and 15 seconds, package and store. A factorial arrangement of A x B (4x3) with two replicates was applied giving a total of 24 treatments in the Infostat statistical program. The investigation showed the following results for the variables pH, acidity, turbidity, density, the stabilizer xanthan gum obtained the best results while for the variable ° brix the stabilizer albumin powder was the best stabilizer. In the difference of color, it was determined that in the treatments where albumin powder was added there was less variation in color. For the sedimentation, it was determined that in the treatments where xanthan gum was added, there was no sedimentation. For the sensory analysis of the fermented beverages, the light color characteristic was the most accepted. For aroma, the respondents rated the beverages as neither unpleasant nor pleasant or unpleasant. For texture, the respondents considered it to be liquid for the powdered albumin treatments and viscous for the xanthan gum treatments, and finally, for acceptability they rated it as neither like nor dislike. The results of the laboratory analysis of Food Control and Analysis of the Technical University of Ambato indicated that the pH of the drinks was between 4.37 and 5.85; the acidity between 0.305 and 1.34; the density was between 1.0252 and 1.0335; the viscosity between 81.4 and 644 and the amount of mesophilic aerobes varied from 1.5 x 107 to 7.4 x 102. In the stability sheet the results were in pH with a value of 4.4 in the first control, up to 4.19 in the third and last control. The acidity that was evaluated in the first control, presented a value of 1.34; and in the last control 1.39. The presence of mesophilic aerobes during the first control was 7.4 x 102 and finally in the third control with 1.1 x 103.